2011
DOI: 10.1377/hlthaff.2010.1024
|View full text |Cite
|
Sign up to set email alerts
|

Proportion Of Antidepressants Prescribed Without A Psychiatric Diagnosis Is Growing

Abstract: Over the past two decades, the use of antidepressant medications has grown to the point that they are now the third most commonly prescribed class of medications in the United States. Much of this growth has been driven by a substantial increase in antidepressant prescriptions by nonpsychiatrist providers without an accompanying psychiatric diagnosis. Our analysis found that between 1996 and 2007, the proportion of visits at which antidepressants were prescribed but no psychiatric diagnoses were noted increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
188
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 28 publications
10
188
2
1
Order By: Relevance
“…However, studies have shown that a high proportion of prescriptions for psychotropic medications such as anxiety medications fail to have a corroborating diagnosis in the medical record. [15][16][17] Our data do not allow confirmation via medical records or other sources.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies have shown that a high proportion of prescriptions for psychotropic medications such as anxiety medications fail to have a corroborating diagnosis in the medical record. [15][16][17] Our data do not allow confirmation via medical records or other sources.…”
Section: Discussionmentioning
confidence: 96%
“…Tamoxifen potentiates the 103,109 Antidepressants are one of the most commonly prescribed medications in the US. [110][111][112] Commonly prescribed antidepressants classified as selective serotonin reuptake inhibitors (SSRIs) inhibit the enzyme CYP2D6 and thus may slow the metabolism of tamoxifen, resulting in a decrease of its potency and thereby increasing the risk of recurrence. [113][114][115][116] Aromatase Inhibitors: Letrozole, Anastrozole, and Exemestane: Aromatase inhibitors (AIs) work by blocking the enzyme aromatase, which converts adrenal androgens into estrogens.…”
Section: Hormonal Blockadementioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) are a class of small molecules that are highly selective for SERT over DAT and NET and that inhibit 5-HT reuptake with nanomolar potency 16 . SSRIs are typically used as antidepressants in the treatment of major depressive disorder and anxiety disorder 1 and are the most widely prescribed antidepressants 17 .…”
Section: Main Textmentioning
confidence: 99%